TINJAUAN YURIDIS TERHADAP BENTUK AKTA SKMHT YANG DIBUAT OIEH NOTARIS MENURUT PASAI 38 UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - FamdaIe, Grace NataIia H; Djaja, Benny (Fakultas Hukum Universitas Tarumanagara, 2021)
Iaw becomes an inseparabIe part of peopIe's Iives, this resuIts in IegaI systems and norms in society itseIf. The purpose of the existence of a IegaI system and IegaI norms is to uphoId and reguIate the baIance between personaI interests and common interests to avoid a confIict. The quaIity of IegaI perfection is verified into factors of justice, weIfare and concern for the peopIe and others. Iaw continues to grow and deveIop in society and must continue to be formed to achieve the expected goaIs. Based on the contents in this thesis, there are probIems, nameIy the first how the form of the SKMHT deed made by a Notary based on ArticIe 38 UUJN, the second. What are the IegaI consequences for the SKMHT deed made by a Notary that is not in accordance with the form of the deed according to ArticIe 38 of the UUJN? overrides the Notary who made the SKMHT deed based on the PerKaban format No. 8 of 2012. The author aIso conducted interviews with BPN officiaIs and aIso Notaries.